Elephantine in context: studies on the history, religion and literature of the Judeans in Persian period Egypt - Kratz, Reinhard Gregor; Schipper, Bernd U. (Forschungen zum Alten Testament, 2022)
"The Persian period has long been considered a "dark era" in Israel's history. For this reason, research has mainly focused on how it is depicted in the Hebrew Bible. A spectacular discovery of archaeological relics and epigraphic sources was hence hardly noticed: the military colony located on the island of Elephantine in the Nile, on the border between Egypt and present-day Sudan. The basic approach of this volume, which documents a three-year Deutsche Forschungsgemeinschaft project, is to break with a research tradition focusing on the Judeans (Jews) mentioned in the Aramaic papyri from Elephantine and instead investigate the military colony in a broader historical context also documented by Demotic and Egyptian-hieratic evidence found at Elephantine. The studies presented focus on three main subject areas: society and administration, religion, and literature. They show that historically the island of Elephantine hosted a multicultural society with several interactions between the Egyptians and the other inhabitants, and that it was also an important administrative centre for the Persian authorities."
Literaturangaben
Keywords: Achaemenid dynasty -- 559-330 B.C -- History; Achaemenid dynasty - 559-330 B.C; Achaemenid dynasty - 559-330 B.C - History; To 1500; Elephantine (Egypt) -- Religion; Éléphantine (Égypte) - Religion; Egypt - Elephantine; Elephantine (Egypt) - Religion; Aufsatzsammlung; Juden; Elephantine; Zeithintergrund; Bibel / Altes Testament; Elephantine-Urkunden; Geschichte 664 v. Chr.-332 v. Chr.; Religion; Alter Orient; Kultur; Diaspora; Ägypten